ANALISIS PEMBIAYAAN USAHA DI BANK SYARIAH - Pradesyah, Riyan; Bara, Al (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
Financing is a function of the activities of Islamic financial institutions that must be carried out If the Islamic financial institution does not carry out financing or distribution of financing, the Islamic financial institution will be subject to sanctions from the Financial Services Authority (OJK) and Bank Indonesia. Islamic financial institutions, have financing that is different from conventional financial institutions, where Islamic financial institutions issue financing with sharia principles. The purpose of this study is to see the financing or financing system carried out by Islamic financial institutions. The method used is literature study. As for the research results obtained, that Islamic financial institutions provide financing by classifying the type of financing; Consumptive and productive. In general, consumptive financing uses a murabaha contract or sale and purchase, while productive financing uses a mudharabah contract or profit sharing agreement.